2017
DOI: 10.1369/0022155417732527
|View full text |Cite
|
Sign up to set email alerts
|

Canine Salivary Glands: Analysis of Rab and SNARE Protein Expression and SNARE Complex Formation With Diverse Tissue Properties

Abstract: The comparative structure and expression of salivary components and vesicular transport proteins in the canine major salivary glands were investigated. Histochemical analysis revealed that the morphology of the five major salivary glands-parotid, submandibular, polystomatic sublingual, monostomatic sublingual, and zygomatic glands-was greatly diverse. Immunoblot analysis revealed that expression levels of α-amylase and antimicrobial proteins, such as lysozyme, lactoperoxidase, and lactoferrin, differed among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Keratinization on the tongue surface is usually determined by the type of food, species with hard food types such as mice and rats Weber and von Ebner glands on its tongue, similar to H. ichneumon (Al-Jumaily et al, 2021;Selim & Samir, 2018) and Canis lupus familiaris (Gomi et al, 2017). PAS staining reacted positively, inducing a magenta stain on the textus muscularis striatus syncytialis layer of the corpus and both lateral sides of the radix on the tongue of the Javan mongoose, indicating the presence of Weber glands, as is the case with H. ichneumon (Selim & Samir, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Keratinization on the tongue surface is usually determined by the type of food, species with hard food types such as mice and rats Weber and von Ebner glands on its tongue, similar to H. ichneumon (Al-Jumaily et al, 2021;Selim & Samir, 2018) and Canis lupus familiaris (Gomi et al, 2017). PAS staining reacted positively, inducing a magenta stain on the textus muscularis striatus syncytialis layer of the corpus and both lateral sides of the radix on the tongue of the Javan mongoose, indicating the presence of Weber glands, as is the case with H. ichneumon (Selim & Samir, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Small G proteins are classified into five families, and regulate various cellular functions. Rap / Rab signaling plays an important role in saliva and amylase secretion ( D'Silva et al, 1998 ; Sabbatini et al, 2008 ; Gomi et al, 2017 ). Our study showed no increase in the expression of mRNA related to receptors for noradrenaline secreted from sympathetic nerves involved in protein secretion, where is the upstream of salivary secretion system, while upregulations of Rap/Rab signaling for transporting intracellular vesicles and v-SNARE (Vamp8) to secrete amylase via exocytosis at apical side of acinar cells were observed in the 1/6 g environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cytological and glycoconjugate histochemical observations of the secretory cells obtained differed from those of the salivary glandular cells. 26 , 43 , 44 According to Martin et al, three types of secretory granules may be present in the acinar cells of canine lacrimal and third eyelid glands. 30 The structural features of the granule type in tubular cells and the most common granule type in acinar cells correspond to our results except for the electron density of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on the expression of these proteins in the exocrine glands of other mammalian species, except for our recent studies. 26 , 27 The lacrimal gland has been described as compound tubuloacinar or tubuloaveolar in structure, but the secretory unit distribution differs among mammalian species. The canine lacrimal gland is generally regarded as a seromucous gland.…”
Section: Introductionmentioning
confidence: 99%